2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591788
|View full text |Cite
|
Sign up to set email alerts
|

Video monitoring of oxygen saturation during controlled episodes of acute hypoxia

Abstract: A method for extracting video photoplethysmographic information from an RGB video stream is tested on data acquired during a porcine model of acute hypoxia. Cardiac pulsatile information was extracted from the acquired signals and processed to determine a continuously reported oxygen saturation (SvidO2). A high degree of correlation was found to exist between the video and a reference from a pulse oximeter. The calculated mean bias and accuracy across all eight desaturation episodes were -0.03% (range: -0.21% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…iPPG is acquired using a video camera instead of a photodetector, under dedicated [19,[22][23][24] or ambient [21,25] light. The video is usually recorded from palm or face regions [21][22][23][24][25].Pilot studies have demonstrated the possibility of extracting iPPG from anesthetized animals, specifically pigs [26,27]. Since iPPG allows easy and non-invasive estimation of pulse rate, this technique would be very useful for NHP studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…iPPG is acquired using a video camera instead of a photodetector, under dedicated [19,[22][23][24] or ambient [21,25] light. The video is usually recorded from palm or face regions [21][22][23][24][25].Pilot studies have demonstrated the possibility of extracting iPPG from anesthetized animals, specifically pigs [26,27]. Since iPPG allows easy and non-invasive estimation of pulse rate, this technique would be very useful for NHP studies.…”
mentioning
confidence: 99%
“…Pilot studies have demonstrated the possibility of extracting iPPG from anesthetized animals, specifically pigs [26,27]. Since iPPG allows easy and non-invasive estimation of pulse rate, this technique would be very useful for NHP studies.…”
mentioning
confidence: 99%